A Novel Immunobiotics Bacteroides dorei Ameliorates Influenza Virus Infection in Mice - Song, Liqiong; Huang, Yuanming; Liu, Guoxing; Li, Xianping; Xiao, Yuchun; Liu, Chang; Zhang, Yue; Li, Jintong; Xu, Jianguo; Lu, Shan; Ren, Zhihong (Frontiers in Immunology, 2022)
Objective Probiotics can modulate immune responses to resist influenza infection. This study aims to evaluate the anti-viral efficacy of B. dorei. Methods C57BL/6J mice were infected with influenza virus together with treatment of PBS vehicle, B. dorei, or oseltamivir respectively. Anti-influenza potency of B. dorei and the underlying mechanism were determined by measuring survival rate, lung viral load and pathology, gene expression and production of cytokines and chemokines, and analysis of gut microbiota. Results Administration of B. dorei increased (by 30%) the survival of influenza-infected mice, and improved their weight loss, lung pathology, lung index, and colon length compared to the vehicle control group. B. dorei treatment reduced (by 61%) the viral load of lung tissue and increased expression of type 1 interferon more rapidly at day 3 postinfection. At day 7 postinfection, B. dorei-treated mice showed lower local (lung) and systemic (serum) levels of interferon and several proinflammatory cytokines or chemokines (IL-1β, IL-6, TNF-α, IL-10, MCP-1 and IP-10) with a efficacy comparable to oseltamivi treatment. B. dorei treatment also altered gut microbiota as indicated by increased levels of Bacteroides, Prevotella, and Lactobacillus and decreased levels of Escherichia, Shigella, and Parabacteroides. Conclusion B. dorei has anti-influenza effect. Its working mechanisms involve promoting earlier interferon expression and down-regulating both local and systemic inflammatory response. B. dorei changes the composition of gut microbiota, which may also contribute to its beneficial effects.